The Impact Of College Of Technology (CoT) Leadership Style On The Performance Of Graduates Joining The Omani Construction Industry - Al-Harthy, Fatma Nasser (2017)
The rapid growth of the Omani construction industry brought upon the need for more qualified and skilled labour to serve the industry. Currently, 92.5% of employment portions is dominated by expatriates. With Omanization policy, the percentage of the expatriates is expected to reduce and replaced by skilled locals. In Oman, Colleges of Technology (CoTs) are key institutions, which are tasked with equipping graduates with the industry required skills. However, the performance of most of the graduates is still below employers’ expectations. The lack of necessary skills and expertise of the locals creates a problem to realise the Omanization policy.